Konseling Bagi Anak yang Mengalami Perilaku Kekerasan - Hesty Nurrahmi (PSGA LP2M IAIN Pontianak, 2015)
The violence behavior on children is often performed by the closest people of them, such as parents, family, and school environment. There are four categories of violence acts on children: negligence, physical assault, psychological and emotional harassment, and sexual harassment. This paper explores the counseling or the supporting towards the children experiencing the violence behaviors. Furthermore, those behaviors include the types of abuse acts, the causes of violence acts, and the counseling given to the children and family that encounter the violence behaviors.